On a class of hybrid integral transformations (Bessel-Fourier-Bessel-...-Fourier-Bessel) on the polar axis with $2n$ junction points - Lenyuk, M. P.; Oleinik, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The hybrid integral transformations (Bessel-Fourier-Bessel-...-Fourier-Bessel) are constructed on the polar axis with $2n$ junction points by using the method of a delta-shaped sequence regarded as a Dirichlet kernel. The principal identity of the integral transformation of a differential operator is obtained.